Spunbonded nonwoven fabric and filter having the same

The spunbond nonwoven fabric, made from specific polyolefin resin and additives, addresses the challenge of balancing dust collection efficiency and pressure loss in filters, while maintaining strength and stability after heating.

JP2025060074APending Publication Date: 2025-04-10TOYOBO MC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023170577
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing filters face challenges in achieving a balance between high efficiency dust collection performance and low pressure loss, while also maintaining tensile strength and dimensional stability after heating.

Method used

A spunbond nonwoven fabric made from polyolefin resin with a melt flow rate of 80g/10min or less, an average fiber diameter of 8.0 to 30 μm, and containing hindered amine additives and magnesium stearate, which is electretized to enhance collection performance and maintain properties after heating.

Benefits of technology

The spunbond nonwoven fabric achieves low pressure loss, excellent balance between collection performance and pressure loss, and maintains tensile strength and dimensional stability even after heating, making it suitable for use in filters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060074000001
    Figure 2025060074000001
  • Figure 2025060074000002
    Figure 2025060074000002
Patent Text Reader

Abstract

To provide a spunbonded nonwoven fabric that has low pressure loss and is excellent in filtration property and processability.SOLUTION: A spunbonded nonwoven fabric of the invention contains fibers made of polyolefin-based resin. Melt flow rate (MFR) of the polyolefin-based resin is 80 g / 10 min or less. Basis weight of the spunbonded nonwoven fabric is 10 to 50 g / m2. Average fiber diameter of the fibers is 8.0 to 30 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spunbond nonwoven fabric and a filter including the same. [Background technology]

[0002] Traditionally, filters have been used to capture and remove pollen, dust, and other particles from gas, and fiber sheets made of fibers such as nonwoven fabric sheets are often used as the filter material for these filters. Filters are required to be able to capture a large amount of microscopic dust, i.e., have high dust capture efficiency, and to have low resistance when gas passes through the filter, i.e., have low pressure loss. In recent years, from the perspective of energy conservation, filters with particularly low pressure loss are in demand.

[0003] The collection mechanism of the filter is mainly due to physical actions such as Brownian diffusion, interception, and inertial collision, and in order to obtain a filter medium with a higher collection efficiency, it is suitable to make the fiber diameter of the fiber sheet used as the filter medium narrower and increase the fiber density of the fiber sheet. However, if the fiber density of the fiber sheet is increased, the void ratio between the fibers in the fiber sheet decreases, resulting in high pressure loss. On the other hand, in order to obtain a filter medium with low pressure loss, it is sufficient to make the fiber diameter of the fiber sheet thicker, but the void ratio between the fibers in the fiber sheet increases, resulting in low collection performance.

[0004] As described above, it is difficult to achieve both high-efficiency collection performance and low pressure loss at the same time, and therefore, in general, fiber sheets made of fibers with a fine fiber diameter are used for applications where high-efficiency collection performance is important, and fiber sheets made of fibers with a thick fiber diameter are used for applications where low pressure loss is important, and so on.

[0005] On the other hand, a technique for improving collection performance regardless of fiber diameter is known in which a fiber sheet is charged and electrostatic action is used in addition to physical action.For example, a method for producing an electret fiber sheet has been proposed in which a fiber sheet is placed in contact with an earth electrode, and high voltage is applied by a non-contact type electrode while the earth electrode and the fiber sheet are moved together to continuously convert the fiber sheet into an electret fiber (Patent Document 1).

[0006] The fiber sheet described in the examples of Patent Document 1 is a melt-blown nonwoven fabric that has been electretized by the application of high voltage. Generally, nonwoven fabrics with narrow fiber diameters, such as melt-blown nonwoven fabrics, have a larger fiber surface area per unit volume than nonwoven fabrics with wide fiber diameters, and a greater charging effect can be obtained, thereby improving collection performance and allowing the fabric to be used in applications where highly efficient collection performance is important. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 61-289177 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the melt-blown nonwoven fabric of Patent Document 1 has a problem that the pressure loss is high, although the balance between pressure loss and collection performance is improved. Even if the pressure loss is reduced by increasing the fiber diameter, the collection performance and dimensions change due to heat applied during the processing stage up to commercialization, such as lamination processing with other sheets and pleating processing, and the tensile strength and tensile elongation properties become insufficient. As a result, there is a problem that processing becomes difficult.

[0009] Therefore, an object of the present invention is to provide a spunbond nonwoven fabric that has low pressure drop and an excellent balance between pressure drop and collection performance, that shows little change in collection performance and dimensions before and after heating, and that has excellent tensile strength and tensile elongation properties even after heating, and a filter using the spunbond nonwoven fabric. [Means for solving the problem]

[0010] In order to solve the above problems, the inventors have conducted extensive research and have finally completed the present invention.

[0011] 1. A spunbond nonwoven fabric made of fibers made of a polyolefin resin, the melt flow rate (MFR) of the polyolefin resin being 80 g / 10 min or less, and the basis weight of the spunbond nonwoven fabric being 10 to 50 g / m 2 and the fibers have an average fiber diameter of 8.0 to 30 μm. 2. Thermal stability coefficient is 0.80 or more, dimensional change rate before and after heating is 5% or less, and tensile strength after heating is 0.8N / 50mm / (g / m 2 2. The spunbond nonwoven fabric according to claim 1, having a tensile elongation after heating of 20% or more. 3. The spunbond nonwoven fabric according to the above 1 or 2, which contains 0.15 to 2 mass% of a hindered amine additive and 0.03 to 0.15 mass% of magnesium stearate. 4. The spunbond nonwoven fabric according to any one of the above 1 to 3, which has been made into an electret. 5. A filter comprising the spunbond nonwoven fabric according to any one of the above 1 to 4. Effect of the Invention

[0012] The present invention can provide a spunbond nonwoven fabric and a filter that have low pressure loss, an excellent balance between pressure loss and collection performance, little change in collection performance and dimensions before and after heating, and excellent tensile strength and tensile elongation properties even after heating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Specific examples of the present invention will be given below, but the most suitable configuration can be selected for each application in accordance with the spirit of the present invention. The spunbond nonwoven fabric of the present invention is a spunbond nonwoven fabric containing fibers made of a polyolefin resin having a melt flow rate (MFR) of 80 g / 10 min or less, and the nonwoven fabric has a basis weight of 10 to 50 g / m 2 The fibers have an average fiber diameter of 8.0 to 30 μm.

[0014] Examples of the polyolefin resin used in the present invention include homopolymers of polypropylene, polyethylene, and polymethylpentene, copolymers of polypropylene, polyethylene, and polymethylpentene with various α-olefins, and mixtures thereof. From the viewpoint of improving the balance between pressure loss and collection performance and cost, homopolymers of polypropylene, polyethylene, and polymethylpentene, and mixtures thereof are preferred. Most preferred are homopolymers of polypropylene, and mixtures of homopolymers of polypropylene, polyethylene, and polymethylpentene.

[0015] The content of the polypropylene homopolymer contained in the polyolefin resin used in the present invention is not particularly limited, but is preferably 30% by mass or more, more preferably 50% by mass or more, and most preferably 80% by mass or more. If the content is less than 30% by mass, problems occur such as a decrease in the balance between pressure loss and collection performance, and insufficient tensile strength and tensile elongation after heating.

[0016] The melt flow rate (MFR) of the polyolefin resin used in the present invention is 80 g / l It is preferable that the melt flow rate (MFR) is 0 min or less, more preferably 60 g / 10 min or less, and further preferably 32 g / 10 min or less. Two or more resins having different melt flow rates (MFR) may be mixed in any ratio to adjust the melt flow rate (MFR). By setting the melt flow rate (MFR) to 80 g / 10 min or less, the thermal stability coefficient is improved, the dimensional change rate is reduced, and the tensile strength and tensile elongation after heating are improved. The lower limit of the melt flow rate of the polyolefin resin used in the present invention is not particularly limited, but if it is 8 g / 10 min or more, there is no problem in practical use. The melt flow rate (MFR) is a value measured at a temperature of 230°C and a load of 2.16 kg in accordance with ASTM D1238.

[0017] The melting point of the polyolefin resin used in the present invention is preferably 120°C or higher and 250°C or lower, more preferably 150°C or higher and 240°C or lower. By setting the melting point to preferably 120°C or higher, more preferably 150°C or higher, not only is the thermal stability coefficient improved, but also heat resistance that can withstand the heat applied in the processing stage is easily obtained. In addition, by setting the melting point to preferably 250°C or lower, more preferably 240°C or lower, it becomes easier to cool the yarn discharged from the spinneret, and fusion between the fibers is suppressed, making it easier to perform stable spinning.

[0018] Furthermore, to the polyolefin resin used in the present invention, additives such as commonly used antioxidants, weather resistance stabilizers, light resistance stabilizers, antistatic agents, antifogging agents, antiblocking agents, lubricants, crystal nucleating agents, and pigments, or other polymers may be added as necessary, within the scope of not impairing the effects of the present invention.

[0019] The spunbonded nonwoven fabric of the present invention can contain additives such as a heat stabilizer, a weathering agent, and a polymerization inhibitor, and from the viewpoint of improving the chargeability and charge retention when the nonwoven fabric is made into an electret, it is preferable that the spunbonded nonwoven fabric contains a hindered amine additive. Also, from the viewpoint of improving the heat stability, it is preferable that the spunbonded nonwoven fabric contains magnesium stearate.

[0020] The content of the hindered amine additive is preferably 0.15 to 2% by mass. The lower limit is more preferably 0.2% by mass or more, and particularly preferably 0.5% by mass or more. In consideration of spinnability, the content is preferably 2% by mass or less.

[0021] The magnesium stearate is preferably contained within the range of 0.03 to 0.15% by mass. The lower limit is preferably 0.04% by mass or more, more preferably 0.07% by mass or more, and in consideration of electrostatic chargeability and spinnability, preferably 0.15% by mass or less.

[0022] Specific examples of the hindered amine additive include poly[((6-(1,1,3,3-tetramethylbutyl)imino-1,3,5-triazine-2,4-diyl)((2,2,6,6-tetramethyl-4-piperidyl)imino)hexamethylene((2,2,6,6-tetramethyl-4-piperidyl)imino)] (manufactured by BASF Japan Ltd., Chimassorb (registered trademark) 944), dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine·N-(2,2,6,6-tetramethyl-4-piperidyl)imino), Polycondensation product of N,N'-1,2-ethanediylbis[N-[3-[[4,6-bis[butyl(1,2,2,6,6-pentamethylpiperidin-4-yl)amino]-1,3,5-triazin-2-yl]amino]propyl]-N',N'-dibutyl-N',N'-bis(1,2,2,6,6-pentamethyl) succinate (manufactured by BASF Japan, Chimassorb(R) 119), dimethyl-1-(2-hydroxyethyl)-4-hydroxy-2-phenylpropanediol (manufactured by BASF Japan, Chimassorb(R) 2020), ,2,6,6-tetramethylpiperidine polycondensate (manufactured by BASF Japan Ltd., TINUVIN (registered trademark) 622), 2-(3,5-di-t-butyl-4-hydroxybenzyl)-2-n-butylmalonate bis(1,2,2,6,6-pentamethyl-4-piperidyl) (manufactured by BASF Japan Ltd., TINUVIN (registered trademark) 144), and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-((hexyl)oxy)-phenol (manufactured by BASF Japan Ltd., TINUVIN (registered trademark) 1577).

[0023] The spunbond nonwoven fabric of the present invention may contain, in addition to the hindered amine additive, additives such as stabilizers such as nitrogen-containing hindered phenols, metal salt hindered phenols, phenols, sulfur, and phosphorus, and crystal nucleating agents. Specifically, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (manufactured by BASF Japan, Irganox (registered trademark) 1010), octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (manufactured by BASF Japan, Irganox (registered trademark) 1076), tris-(3,5-di-t-butyl-4-hydroxybenzyl)-isocyanurate (manufactured by BASF Japan, Irganox (registered trademark) 3114), N,N'-hexane-1,6-diylbis(3-(3,5-di-t-butyl-4-hydroxyphenylpropionate), etc. amide (Irganox® 1098, manufactured by BASF Japan Ltd.), 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol (Irganox® 565, manufactured by BASF Japan Ltd.), 3,9-bis-{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)-propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro-[5,5]undecane (Sumitomo Chemical Co., Ltd., Sumilizer® GA-80), and Irgaclear® XT386, manufactured by BASF Japan Ltd.

[0024] In addition, additives having various functions such as dust removal, deodorization, antibacterial, antifungal, antiviral, insect repellent, insecticidal, pest repellent, harmful substance removal, fragrance, dehumidification, humidity control, moisture absorption (drying), moisture (humidity) transmission, adsorption of oil, etc., adjustment of ion balance such as cation adsorption, and evaporation or sustained release of water, volatile drugs, etc. may be added.

[0025] It is also important that the fibers constituting the spunbonded nonwoven fabric of the present invention have an average fiber diameter of 8.0 to 30.0 μm. By making the average fiber diameter preferably 10.0 μm or more, more preferably 12.0 μm or more, it is possible to prevent a decrease in spinnability and produce a nonwoven fabric of good quality stably. On the other hand, by making the average fiber diameter preferably 28.0 μm or less, more preferably 25.0 μm or less, it is possible to obtain high density and uniformity, excellent processing characteristics that can withstand practical use, and high collection efficiency when the spunbonded nonwoven fabric is used to make an air filter.

[0026] The cross-sectional shape of the fibers constituting the spunbonded nonwoven fabric of the present invention is not particularly limited as long as the resulting spunbonded nonwoven fabric is suitable for filter applications, but preferred shapes are circular, hollow circular, elliptical, flat, irregular shapes such as X-shaped and Y-shaped, polygonal, multi-lobed, etc. The fiber diameter of non-circular fibers is calculated by taking the circumscribing circle and the inscribing circle of the fiber cross section and averaging the diameters of the circles.

[0027] It is important that the spunbond nonwoven fabric of the present invention is made into an electret. By making it into an electret, it is possible to obtain high collection performance while maintaining low pressure loss due to the electrostatic adsorption effect.

[0028] The spunbond nonwoven fabric of the present invention may be laminated with other sheets to form a laminated fiber sheet. For example, the spunbond nonwoven fabric may be laminated with a sheet having a higher rigidity to improve the strength of the product. It is preferable to use the spunbond nonwoven fabric of the present invention in combination with a sheet having a deodorizing, antibacterial, etc. Furthermore, filters and filter units using the spunbond nonwoven fabric of the present invention are also included in the scope of the present invention.

[0029] The thermal stability coefficient of the spunbonded nonwoven fabric of the present invention is preferably 0.80 or more, and the dimensional deformation rate before and after heating is preferably 5% or less. The calculation of the thermal stability coefficient and the dimensional change rate will be described in detail in the following examples. The thermal stability coefficient is preferably 0.80 or more, more preferably 0.85 or more, and even more preferably 0.90 or more. By being in this range, a filter with high collection efficiency can be obtained without decreasing the charging performance when the spunbonded nonwoven fabric is processed into a filter. The upper limit of the thermal stability coefficient is 1.0, which indicates that there is no performance deterioration due to heat. The dimensional change rate before and after heating is preferably 5% or less, and more preferably 3% or less. This range can reduce deformation and processing defects during thermal processing. The lower limit of the dimensional change rate before and after heating is 0, which indicates no change.

[0030] The spunbond nonwoven fabric of the present invention has a tensile strength after heating of 0.8 N / 50 mm / (g / m 2 The tensile strength after heating is preferably 0.8N / 50mm / (g / m 2 ) or more, preferably 1.0N / 50mm / (g / m 2 ) or more, the sheet can be processed without breaking. There is no upper limit to the tensile strength after heating, but it is preferably 2.0N / 50mm / (g / m 2 ) The following is preferred from the viewpoint of manufacturing.

[0031] In addition, the tensile elongation at the maximum strength of the tensile strength, i.e., the tensile strength after heating, is preferably 20% or more, more preferably 25% or more, so that the sheet can be processed without breaking during molding, etc. There is no upper limit to the tensile strength after heating, but 80% or less is preferable from the viewpoint of production.

[0032] (Average fiber diameter [μm]) Ten small samples were randomly taken from the nonwoven fabric and photographed at 500 to 3000 times magnification using a scanning electron microscope. The fiber diameters of 10 fibers from each sample, a total of 100 fibers, were measured and the average value was calculated by rounding off to the first decimal place.

[0033] (Weight [g / m 2 ]) In accordance with Section 6.2 of JIS L1913:2010, three samples measuring 50 cm x 50 cm were taken, the weight of each sample was measured, and the average value obtained was converted to a value per unit area and rounded off to the first decimal place.

[0034] (Electret treatment) Spunbond nonwoven fabric with a breathability of 120 cm 3 / cm 2 The sheet was placed on a mesh support (96 mesh) with a flow rate of 100 / s, and the aqueous solution was sprayed at a pressure of 0.5 MPa from a nozzle with a diameter of 0.1 mmφ and a pitch of 0.6 mm located 2 cm above the nonwoven sheet. The aqueous solution was high-purity water obtained by subjecting ordinary tap water to reverse osmosis membrane treatment and then ion exchange membrane treatment. The conveying speed of the mesh support was 4 m / min, and the area below the mesh support directly below the nozzle was reduced to a reduced pressure of 2 mAq. This treatment was performed twice on both sides of the sheet. The sheet was then dried by retaining it in a hot air oven at 80°C for 1 minute. As a result, an electret spunbond nonwoven fabric was obtained.

[0035] (Filtration characteristics QF) The pressure loss PD [mmAq] was determined by placing a sample of electret spunbond nonwoven fabric in a duct, controlling the linear velocity passing through the filter medium to 10.4 cm / sec, and reading the static pressure difference between the upstream and downstream of the sample with a pressure gauge. The particle collection efficiency E [%] was evaluated using a filter tester with an average particle diameter of 0.3 μm. The experiment was carried out using atmospheric dust particles at a wind volume of 10.4 cm / sec. The filtration efficiency QF [1 / mmAq] was calculated from the pressure loss PD [mmAq] and the particle collection efficiency E [%] using the following formula. QF can represent the balance between pressure loss and particle collection efficiency. QF=-Ln((100-E) / 100) / PD

[0036] (Thermal Stability Coefficient) The electret spunbond nonwoven fabric was placed in a dryer at 100° C. for 30 minutes for heat treatment, and the ratio of the QF values ​​before and after this heat treatment was calculated as the thermal stability coefficient based on the following formula. Heat stability factor = QF after heat treatment / QF before heat treatment

[0037] (Dimensional change rate) The electret spunbond nonwoven fabric was cut into a sample of 10 cm x 10 cm and heat-treated by placing it in a dryer at 140°C for 3 minutes. The lengths of the four sides of the nonwoven fabric after this heat treatment were measured to calculate the area, and the dimensional change rate [%] before and after heating was calculated using the following formula. Dimensional change rate [%] = (1 - area after heat treatment / area before heat treatment) x 100

[0038] (Tensile strength and tensile elongation after heating) The electretized spunbond nonwoven fabric was heat-treated by leaving it in a dryer at 100°C for 30 minutes, and a tensile test was performed in the longitudinal direction of the nonwoven fabric in accordance with JIS L1913:2010, Section 6.3.1, under the conditions of a sample size of 50mm x 200mm, grip interval of 150mm, and a pulling speed of 200mm / min. The test was performed on three samples, and the arithmetic mean value of the maximum strength [N / 50mm] when the sample was pulled until it broke was divided by the basis weight of the nonwoven fabric to obtain the tensile strength [N / 50mm / (g / m 2 The arithmetic mean value of the elongation at break was calculated as the tensile elongation [%]. The machine direction of the nonwoven fabric refers to the machine direction (MD) during the production of the nonwoven fabric.

[0039] <Example 1> Polypropylene resin (Lotte Chemical's FR-170, MFR 26g / 10min) was mixed with 1.0% by mass of a hindered amine additive (BASF's Chimassorb 944) and 0.075% by mass of magnesium stearate, and spun at a single hole output rate of 0.6g / min by the spunbond method. The spun yarn was cooled and solidified by blowing cold air onto it, and then pulled and stretched by compressed air at an ejector pressure of 124kPa, and collected on a moving net to obtain a nonwoven web made of polypropylene long fibers with an average fiber diameter of 20μm. The spinning speed calculated from this was 2810m / min. No yarn breakage was observed, and the spinnability was good.

[0040] Furthermore, using a metal embossing roll with an upper roll engraved with a diamond pattern and an adhesive area of ​​11%, embossing was performed at a line pressure of 50 kN / m and a temperature of 130°C, resulting in a basis weight of 30 g / m. 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 1.

[0041] <Example 2> A nonwoven fabric web made of polypropylene long fibers having an average fiber diameter of 13 μm was obtained in the same manner as in Example 1, except that the single-hole discharge rate was 0.4 g / min and the ejector pressure was 310 kPa. The spinning speed calculated from this was 4550 m / min. No yarn breakage was observed, and the spinnability was good.

[0042] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 20 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 1.

[0043] <Example 3> A nonwoven web made of polypropylene long fibers having an average fiber diameter of 10 μm was obtained in the same manner as in Example 1, except that the single-hole discharge rate was 0.3 g / min and the ejector pressure was 450 kPa. The spinning speed calculated from this was 5500 m / min. No yarn breakage was observed, and the spinnability was good.

[0044] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 15 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 1.

[0045] <Example 4> A nonwoven web made of polypropylene long fibers having an average fiber diameter of 20 μm was obtained in the same manner as in Example 1, except that 0.2 mass% of a hindered amine additive (Chimasorb 944 manufactured by BASF) and 0.04 mass% of magnesium stearate were added to a polypropylene resin (FR-170 manufactured by Lotte Chemical Co., Ltd., MFR 26 g / 10 min). The spinning speed calculated from this was 2810 m / min. No thread breakage was observed, and the spinnability was good.

[0046] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 30 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 1.

[0047] <Example 5> A nonwoven fabric web made of polypropylene long fibers having an average fiber diameter of 9 μm was obtained in the same manner as in Example 3, except that 0.7% by mass of a hindered amine additive (BASF's Chimassorb 2020) and 0.05% by mass of magnesium stearate were added to a polypropylene resin (Prime Polymer's S119, MFR 60 g / 10 min). The spinning speed calculated from this was 7100 m / min. The spinnability was good. No thread breakage was observed, and the spinnability was good.

[0048] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 15 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 1.

[0049] <Example 6> A nonwoven fabric web made of polypropylene long fibers having an average fiber diameter of 25 μm was obtained in the same manner as in Example 1, except that 1.0 mass% of a hindered amine additive (BASF's Chimassorb 944) and 0.075 mass% of magnesium stearate were added to a polypropylene resin (Prime Polymer's Y-2000GV, MFR 18 g / 10 min). The spinnability was good.

[0050] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 30 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 1.

[0051] <Example 7> A nonwoven fabric web made of polypropylene long fibers having an average fiber diameter of 17 μm was obtained in the same manner as in Example 1, except that 1.0% by mass of a hindered amine additive (BASF's Chimassorb 2020) and 0.075% by mass of magnesium stearate were added to a polypropylene resin (LG Chemical's H7700, MFR 34 g / 10 min). The spinning speed calculated from this was 3900 m / min. The spinnability was good.

[0052] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 30 g / m 2The spunbonded nonwoven fabric was obtained. The obtained spunbonded nonwoven fabric was made into an electret, and the filtration characteristics, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation were measured and evaluated. The results are shown in Table 1. The results are shown in Table 1.

[0053] <Example 8> A nonwoven web made of polypropylene long fibers having an average fiber diameter of 18 μm was obtained in the same manner as in Example 1, except that 1.0 mass% of a hindered amine additive (Chimasorb 944 manufactured by BASF) and 0.075 mass% of magnesium stearate were added to a polypropylene resin (H7700 manufactured by LG Chemical, MFR 34 g / 10 min) and the single-hole discharge rate was 0.9 g / min. The spinning speed calculated from this was 5500 m / min. No thread breakage was observed, and the spinnability was good.

[0054] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 45 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 1.

[0055] <Comparative Example 1> A nonwoven web made of polypropylene long fibers having an average fiber diameter of 35 μm was obtained in the same manner as in Example 1, except that 0.1 mass% of a hindered amine additive (BASF's Chimassorb 944) and 0.02 mass% of magnesium stearate were added to a polypropylene resin (Lotte Chemical's FR-170, MFR 26 g / 10 min), the single-hole discharge rate was 0.9 g / min, and the ejector pressure was 29 kPa. The spinning speed calculated from this was 1400 m / min. No thread breakage was observed, and the spinnability was good.

[0056] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 45 g / m 2 The obtained spunbond nonwoven fabric was made into an electret, and the filtration properties, thermal stability coefficient, dimensional change rate, tensile strength and tensile elongation after heating were measured and evaluated. The results are shown in Table 2.

[0057] <Comparative Example 2> A nonwoven web made of polypropylene long fibers having an average fiber diameter of 20 μm was obtained in the same manner as in Example 1, except that 0.1 mass% of a hindered amine additive (Chimasorb 944 manufactured by BASF) and 0.02 mass% of magnesium stearate were added to a polypropylene resin (H7900 manufactured by LG Chemical, MFR 230 g / 10 min). The spinning speed calculated from this was 2810 m / min. No thread breakage was observed, and the spinnability was good.

[0058] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 30 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 2.

[0059] <Comparative Example 3> The same procedure as in Example 1 was repeated except that only 0.5% by mass of a hindered amine additive (BASF's Chimassorb 944) was added to a polypropylene resin (LG Chemical's H7900, MFR 230 g / 10 min) and the single-hole discharge rate was set to 1.2 g / min. A nonwoven web made of 100 μm long polypropylene fibers was obtained. The spinning speed calculated from this was 5700 m / min. No yarn breakage was observed, and the spinnability was good.

[0060] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 60 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 2.

[0061] <Comparative Example 4> A nonwoven web made of polypropylene long fibers having an average fiber diameter of 20 μm was obtained in the same manner as in Example 1, except that 1.0 mass% of a hindered amine additive (Chimasorb 944 manufactured by BASF) and 0.075 mass% of magnesium stearate were added to a polypropylene resin (H7910 manufactured by LG Chemical, MFR 950 g / 10 min). The spinning speed calculated from this was 2810 m / min. No thread breakage was observed, and the spinnability was good.

[0062] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 30 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 2.

[0063] <Comparative Example 5> A nonwoven web made of polypropylene long fibers having an average fiber diameter of 7 μm was obtained in the same manner as in Example 5, except that 0.7% by mass of a hindered amine additive (BASF's Kimassorb 2020) and 0.05% by mass of magnesium stearate were added to a polypropylene resin (Lotte Chemical's FM-1912, MFR 1200 g / 10 min). The spinning speed calculated from this was 11000 m / min. The spinnability was good. No thread breakage was observed, and the spinnability was good.

[0064] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 15 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 2.

[0065] <Comparative Example 6> A nonwoven fabric web made of polypropylene long fibers having an average fiber diameter of 7 μm was obtained in the same manner as in Example 5, except that 0.5 mass% of a hindered amine additive (Chimasorb 944 manufactured by BASF) and 0.05 mass% of magnesium stearate were added to a polypropylene resin (HP461Y manufactured by LyondellBasell, MFR 1300 g / 10 min). The spinning speed calculated from this was 11000 m / min. The spinnability was good. No thread breakage was observed, and the spinnability was good.

[0066] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 15 g / m 2 The spunbonded nonwoven fabric was made into an electret and was evaluated for its filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation. The results are shown in Table 2.

[0067] <Comparative Example 7> A nonwoven web made of polypropylene long fibers having an average fiber diameter of 20 μm was obtained in the same manner as in Example 1, except that 2.5 mass% of a hindered amine additive (Chimasorb 944 manufactured by BASF) and 0.2 mass% of magnesium stearate were added to a polypropylene resin (H7914 manufactured by LG Chemical, MFR 1400 g / 10 min). The spinning speed calculated from this was 2810 m / min. No thread breakage was observed, and the spinnability was good.

[0068] Furthermore, embossing was carried out in the same manner as in Example 1, and the basis weight was 30 g / m 2 Spunbond nonwoven The obtained spunbond nonwoven fabric was made into an electret, and the filtration properties, thermal stability coefficient, dimensional change rate, tensile strength after heating, and tensile elongation were measured and evaluated. The results are shown in Table 2.

[0069] [Table 1]

[0070] [Table 2]

[0071] From the results of Tables 1 and 2, it can be seen that, as in the examples, the melt flow rate of the resin constituting the spunbond nonwoven fabric is 80 g / 10 min, and the basis weight is 10 to 50 g / m 2 By setting the average fiber diameter of the constituent fibers to 8.0 to 30.0 μm, it is clear that a spunbond nonwoven fabric is obtained that has an excellent balance between pressure loss and collection performance (QF), has little change in collection performance and dimensions before and after heating, and has excellent tensile strength and tensile elongation properties even after heating. [Industrial Applicability]

[0072] INDUSTRIAL APPLICABILITY The present invention can provide a spunbond nonwoven fabric having low pressure loss and excellent filtration properties and processability, thereby making a great contribution to the industrial world.

Claims

1. A spunbond nonwoven fabric containing fibers made of a polyolefin resin, The melt flow rate (MFR) of the polyolefin resin is 80 g / 10 min or less, The weight of the spunbond nonwoven fabric is 10 to 50 g / m 2 and A spunbond nonwoven fabric, characterized in that the average fiber diameter of the fibers is 8.0 to 30 μm.

2. Thermal stability coefficient of 0.80 or more; Dimensional change rate before and after heating is 5% or less. The tensile strength after heating is 0.8 N / 50 mm / (g / m 2 ) The above.

2. The spunbond nonwoven fabric according to claim 1, characterized in that the tensile elongation after heating is 20% or more.

3. 3. The spunbond nonwoven fabric according to claim 1, further comprising 0.15 to 2% by mass of a hindered amine additive and 0.03 to 0.15% by mass of magnesium stearate.

4. 3. The spunbond nonwoven fabric according to claim 1, which is electret.

5. A filter comprising the spunbond nonwoven fabric according to claim 1 or 2.

Citation Information

Patent Citations

  • Production of electret fibrous sheet

    JP1986289177A